Finding work the eBay way. - Svoboda, E.
When software engineer, Gus Grubba, and his team of Silicon Valley programmers lost their jobs to Canadian outsourcing at the digital media company, Discreet, a division of Autodesk Inc. in San Rafael, CA, they decided to put themselves up for auction on eBay. Using the handle "Team offshored," they let online bidders outdo each other to purchase exclusive rights to negotiate a contract with them. Bidding opened the last week of March and continued through early April, with a starting minimum of US 250 dollars for the contract rights and the stipulation that all money from the winning bid would be donated to the George Lucas Educational Foundation. While the scheme wasn't an instant success, it eventually paid off after some media outlets began writing about the team's advertisement.
Keywords: eBay; Human resources; Online auction; Outsourcing; Programmers; Three-dimensional graphics